Experimental analysis of recommended corneal incision sizes in cataract surgery using 13 intraocular lens injector systems - Friedrich, Maximilian; Auffarth, Gerd U.; Merz, Patrick (Scientific reports, 2023)
Smaller corneal incisions in cataract surgery are linked with a better visual outcome and less frequent postoperative endophthalmitis. The insertion of intraocular lens (IOL) injector systems into the anterior chamber of the eye to implant an IOL is associated with incision enlargement (IE) impeding these positive effects. The aim of this study was to compare manufacturers’ recommended incision sizes (IS) of 13 different intraocular lens injector systems in regard of intraoperative IE and postoperative IS. In total, 499 corneal incisions in ex vivo porcine eyes were analyzed. The preoperative ISs depended on the recommended IS of the examined injector system. The IS was measured right before and after IOL injector insertion with an incision gauge set. There was intraoperative IE in 87% of the incisions with a mean IE of 0.26 ± 0.18 mm. IE was often significantly larger in small IS compared to larger IS concerning an injector system (P < 0.05). Five injector systems needed to have a significantly larger IS than the manufacturers’ recommended IS with an average difference of 0.3 mm when applying study criteria (P < 0.05). Thus, the present study shows that IS recommendations require to be critically analyzed by ophthalmic surgeons to enable evidence-based practice.
Veröffentlicht: 15. Februar 2023
Gesehen am 31.07.2023